Transmission strategies for MISO downlink MC-CDMA mobile systems - Silva, Adão
This paper proposes two space-frequency schemes with a multi-user pre-filtering technique for downlink (DL) multicarrier code division multiple access (MC-CDMA) systems. We consider the use of antenna arrays at the base station (BS) and a single antenna at the mobile terminal (MT) and derive the proposed multi-user pre-filtering technique that modulates the transmitted signal to eliminate the effects of multiple access interference (MAI) and channel distortions at the mobile terminals, while maintaining low MT complexity. Two types of detectors are considered at the MT: simple despreading and single user equalizers. The performances of the proposed schemes are compared to those of other transmit signal design approaches that have been recently proposed for DL MC-CDMA, considering both typical indoor and pedestrian scenarios, and channel coding based on UMTS specifications. © Springer Science+Business Media, LLC. 2009.